2016
DOI: 10.1186/s12887-016-0545-6
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in haematological and biochemical reference values for healthy young children in The Gambia

Abstract: BackgroundHaematological and biochemistry reference values for children are important for interpreting clinical and research results however, differences in demography and environment poses a challenge when comparing results. The study defines reference intervals for haematological and biochemistry parameters and examines the effect of seasonality in malaria transmission.MethodsBlood samples collected from clinically healthy children, aged 12–59 months, in two surveys during the dry and wet season in the Upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
1
15
0
2
Order By: Relevance
“…9 Clinical complications such as anemia, pulmonary edema, hypoglycemia, cerebral malaria, puerperal sepsis, miscarriage, premature delivery, low birth weight, congenital infection, and/or perinatal death are possible outcomes of malaria infection during pregnancy. [10][11][12][13][14][15][16] It is pertinent to note however that anemia is especially problematic because hemoglobin level falls due to greater expansion of plasma volume relative to increase in red RBC volume, especially so in the second trimester of cases. It has been shown that anemia increase when there is elevated number of malaria cases 17 and the incidence of anemia during pregnancy is aggravated in malaria high-transmission settings.…”
Section: Introductionmentioning
confidence: 99%
“…9 Clinical complications such as anemia, pulmonary edema, hypoglycemia, cerebral malaria, puerperal sepsis, miscarriage, premature delivery, low birth weight, congenital infection, and/or perinatal death are possible outcomes of malaria infection during pregnancy. [10][11][12][13][14][15][16] It is pertinent to note however that anemia is especially problematic because hemoglobin level falls due to greater expansion of plasma volume relative to increase in red RBC volume, especially so in the second trimester of cases. It has been shown that anemia increase when there is elevated number of malaria cases 17 and the incidence of anemia during pregnancy is aggravated in malaria high-transmission settings.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings of higher platelet counts and lower haemoglobin concentration in the rainy season corroborate a recent study in 12 to 23-month-old Gambian children, whereas contrastingly the Gambian study also found higher total leukocyte, monocyte and neutrophil counts in the rainy season. 7 Higher total leukocyte counts were also found in another Gambian study of infants below one year of age. 3 Of note, the latter Gambian study found that besides rainy season sampling, rainy season births were positively associated with total leukocyte and lymphocyte counts, which remained significant at later ages in infancy.…”
Section: Discussionmentioning
confidence: 67%
“… 4 Haematological values of infants have been shown to differ between Europe and Africa 5 and may also differ between the genetically diverse African populations; moreover, haematological values and normal ranges change with age, particularly in early life. 4 , 6 , 7 Hence, haematological parameters may be specific to location, season, sex and age. As haematology and biochemistry values are used as diagnostic tools by clinicians and as safety and toxicity indicators in clinical trials, population-specific reference ranges are important.…”
Section: Introductionmentioning
confidence: 99%
“…При этом уровень моноцитов и эозинофилов превышал соответствующие значения в сравнении с аналогичными показателями в западных странах. Наряду с этим выявлены существен-ные различия значений гематологических показате-лей разных субпопуляций жителей Африки, связанные с климатом, областью проживания, этнической принад-лежностью [8][9][10]. По результатам ряда исследований, проведенных в странах Азии, также получены данные, указывающие на более низкие референсные значения показателей периферической крови в сравнении с нор-мами, принятыми в западных странах [6,9,11].…”
Section: обоснованиеunclassified
“…Более высокие показатели уровня эритроцитов и гемоглобина имели юноши, в то время как у деву-шек был зарегистрирован высокий уровень лейкоцитов и СОЭ. Данные гендерные различия соответствовали национальным нормативным документам и результа-там исследований, проведенных в различных странах Европы, Азии и Африки [10,15,16].…”
Section: дополнительные результаты исследованияunclassified